Disaster Health Literacy, Risk Perception, and Preparedness towards Resilience in a Volcano-Prone Community: A Cross-sectional Study in Yogyakarta, Indonesia - I Made Moh. Yanuar Saifudin (Journal of Community Empowerment for Health, 2023)
Communities residing in proximity to volcanoes face inherent risks from lahars. The eruption of Indonesia's Merapi volcano in 2010 had far-reaching consequences, impacting multiple districts and leading to 386 fatalities, as well as substantial financial losses amounting to approximately US$403 million. In order to bolster disaster response and mitigation efforts, resilience plays a crucial role by considering hazards, risks, vulnerability, and capacity. This research aimed to examine the relationship between disaster health literacy, risk perception, and preparedness, with the ultimate goal of enhancing resilience within a community susceptible to volcanic activities. The study utilized a cross-sectional design, involving 258 participants residing in hazard zone III areas near Yogyakarta's Merapi mountain, selected through proportional clustered sampling. Between January and February 2023, the researchers employed several assessment tools, including the Indonesian versions of the communities advancing resilience toolkit (CART-AS), disaster health literacy mitigation and preparedness questionnaire (DHLQ), disaster risk perception questionnaire (DRPQ), and disaster preparedness questionnaire (DPQ). The collected data underwent analysis utilizing descriptive statistics and the Pearson correlation test. The results unveiled disaster health literacy (β=0.22, p<0.001), risk perception (β=0.26, p<0.001), and preparedness (β=0.38, p<0.001) were all significant predictors of disaster resilience in a volcano-prone community. In conclusion, this study underscores the significant interplay between disaster health literacy, risk perception, and preparedness in relation to disaster resilience. It emphasizes the significance of fortifying disaster health literacy, fostering accurate risk perception, and promoting preparedness measures to enhance overall resilience in the face of disasters. These findings highlight the necessity for targeted interventions and educational programs aimed at augmenting disaster health literacy, improving risk perception, and enhancing preparedness levels within communities, thereby bolstering their resilience and response capabilities effectively.